Current Approaches to Glycoprotein Analysis - K. Hagan, Andrew; Wang, Maomao; Liu, Li (Protein and Peptide Letters, 2014)
Glycoproteins are becoming increasingly relevant in therapeutics, including tissue plasminogen activator for the treatment of myocardial infarction and strokes, erythropoietin for anemia and various monoclonal antibody–based treatments for cancer. Protein N- and O-glycosylation is perhaps the most crucial and immensely complex posttranslational modification that proteins undergo, and its characterization presents a major challenge. This review will discuss current techniques for the characterization of glycoproteins, with a focus on therapeutic glycoproteins where available. The crucial analytical techniques, such as high-performance liquid chromatography (HPLC), capillary electrophoresis (CE), and mass spectrometry (MS) will be described, alongside the necessary chemical labeling methods for sensitive detection. The well-established chemical and enzymatic methods for oligosaccharide release from proteins will be discussed, as will more modern methods based on exhaustive protein hydrolysis with non-specific proteases.
Keywords: proteases